Effect of fiber hybridization on concrete slurry waste composite containing de-oiled bleaching earth - Sheikh Mohd Iqbal S Zainal Abidin; Nor Mashitah Adnan; Ahmad Nurfaidhi Rizalman; Hidayati Asrah; Fuei, Pien Chee; Mivolil Duinong (Elsevier, 2025)
Concrete Slurry Waste (CSW) is a byproduct of the concrete production industry, consisting of aggregates, minerals, and chemical admixtures. This waste poses environmental risks when disposed of in landfills and has significant limitations to be repurposed for alternative applications. Hence, this study attempts to enhance the performance of CSW by incorporating De-Oiled Bleaching Earth (DOBE) natural pozzolan and hybrid fiber reinforcements. A total of 17 new mixture designs were formulated, utilizing combinations of copper-coated steel, nylon, and basalt fibers, along with varying percentages of DOBE. Initially, the properties of the fibers, DOBE, and CSW were characterized. The developed Hybrid Fiber Reinforced Slurry (HybFRS) were then evaluated for setting time, drying shrinkage, water absorption, compressive strength, and flexural strength. Ultimately, the study examined the synergistic combinations of the hybrid fibers and the interactions between the fibers in CSW containing DOBE. The results indicated that the HybFRS led to increased setting times, significant reductions in drying shrinkage, and minimal changes in water absorption. The mechanical properties of the HybFRS varied with the percentage of DOBE added. The steel-nylon hybrid consistently showed the lowest performance in both compression and flexure across all percentages of DOBE additions. In contrast, the nylon-basalt hybrid performed best at 5 % DOBE, while the basalt-steel hybrid achieved the highest results at 10 % DOBE. The compressive and flexural strengths of these two hybrids were directly related to the percentage of DOBE included in the mixtures.